2019
DOI: 10.1096/fj.201901721r
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of human folypolyglutamate synthetase alters programming and plasticity of somatic cells

Abstract: Folates are vital cofactors for the regeneration of S-adenosyl methionine, which is the methyl source for DNA methylation, protein methylation, and other aspects of one-carbon (C1) metabolism. Thus, folates are critical for establishing and preserving epigenetic programming. Folypolyglutamate synthetase (FPGS) is known to play a crucial role in the maintenance of intracellular folate levels. Therefore, any modulation in FPGS is expected to alter DNA methylation and numerous other metabolic pathways. To explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Polyglutamate forms of folates cannot be expelled to the extracellular compartment, and FPGS activity is fundamental for intracellular folate retention [39]. Consequently, a human cell line with a null mutation in FPGS showed a decrease in its proliferation rate, which was related to a reduction in DNA methylation and suggesting that epigenetic alteration may explain differential expression patterns of genes related to cell division and differentiation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Polyglutamate forms of folates cannot be expelled to the extracellular compartment, and FPGS activity is fundamental for intracellular folate retention [39]. Consequently, a human cell line with a null mutation in FPGS showed a decrease in its proliferation rate, which was related to a reduction in DNA methylation and suggesting that epigenetic alteration may explain differential expression patterns of genes related to cell division and differentiation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid: Folic acid is first metabolized to dihydrofolate and then to tetrahydrofolate, taking part in DNA synthesis, influencing DNA and histone methylation[ 105 ]. Several studies have elucidated the role of folate metabolism in regulating of the epigenetic landscape of stem cells[ 114 , 115 ]. Li et al [ 116 ] have shown that folic acid deficiency in NSCs decreased cell proliferative capacity but increased apoptosis.…”
Section: Other Potential Influential Factorsmentioning
confidence: 99%
“…The status of cancer cells can be reprogrammed through metabolic remodeling while their dedifferentiation ability for the induced stem-like phenotype is maintained [2022]. This capability of switching between differentiated somatic and stem cell states is called cell plasticity [23]. When performing tumor therapy, both genomic instability and microenvironment-driven selection support tumor heterogeneity and enable the development of resistant cells with stem-like properties because of cell plasticity [24].…”
Section: Introductionmentioning
confidence: 99%